Bodies, borders, believers ancient texts and present conversations : essays in honor of Turid Karlsen Seim on her 70th birthday - Seim, Turid Karlsen 1945-2016; Grung, Anne Hege 1965-; Kartzow, Marianne Bjelland 1971-; Solevåg, Anna Rebecca (Eugene Wipf and Stock Publishers, 2015)
This stimulating collection of essays by prominent scholars honors Turid Karlsen Seim. Bodies, Borders, Believers brings together biblical scholars, ecumenical theologians, archeologists, classicists, art historians, and church historians, working side by side to probe the past and its receptions in the present. The contributions relate in one way or another to Seim's broad research interests, covering such themes as gender analysis, bodily practices, and ecumenical dialogue. The editors have brought together an international group of scholars, and among the contributors many scholarly traditions, theoretical orientations, and methodological approaches are represented, making this book an interdisciplinary and border-crossing endeavor. A comprehensive bibliography of Seim's work is included
Pages:1 to 25 -- Pages:26 to 50 -- Pages:51 to 75 -- Pages:76 to 100 -- Pages:101 to 125 -- Pages:126 to 150 -- Pages:151 to 175 -- Pages:176 to 200 -- Pages:201 to 225 -- Pages:226 to 250 -- Pages:251 to 275 -- Pages:276 to 300 -- Pages:301 to 325 -- Pages:326 to 350 -- Pages:351 to 375 -- Pages:376 to 400 -- Pages:401 to 425 -- Pages:426 to 450 -- Pages:451 to 472
Keywords: Bible; Sociologie religieuse; Social scientific criticism of sacred works; Religion and sociology; Sociology, Biblical; Religionssociologi